2021
DOI: 10.3389/fpsyg.2021.723732
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Negative Affect in Emotional Processing of Food-Related Images in Eating Disorders and Obesity

Abstract: The aim of the present study was to analyze differences in the emotional processing (valence, arousal, and dominance) of food-related information in patients with eating disorders (ED), patients with obesity, and healthy women. Moreover, the mediator role of negative affect and the moderating role of the diagnostic group (ED vs. non-ED) were analyzed. Method: The sample consisted of 94 women (39 with eating disorders, 19 with obesity, and 36 healthy participants). Measures: International Affective Picture Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…They are also more predisposed to dysfunctional processing of emotions related to food information [81]. In this study, reduced control over emotions and reduced attraction to food pictures were mediated by negative affect, supporting the predictive role of negative affect in ED symptomatology [81]. The use of inappropriate emotion regulation strategies in response to the situational demand is a feature of various psychiatric disorders [82], suggesting that emotional eating may reflect a dysregulation of emotion processing in patients with EDs.…”
Section: Nonhomeostatic Factors Food Reward and Emotional Eatingsupporting
confidence: 56%
See 1 more Smart Citation
“…They are also more predisposed to dysfunctional processing of emotions related to food information [81]. In this study, reduced control over emotions and reduced attraction to food pictures were mediated by negative affect, supporting the predictive role of negative affect in ED symptomatology [81]. The use of inappropriate emotion regulation strategies in response to the situational demand is a feature of various psychiatric disorders [82], suggesting that emotional eating may reflect a dysregulation of emotion processing in patients with EDs.…”
Section: Nonhomeostatic Factors Food Reward and Emotional Eatingsupporting
confidence: 56%
“…Research has shown that patients with EDs are more predisposed to experience alexithymia (i.e., difficulty identifying and describing feelings) [79], maladaptive emotion regulation [62,75,78], and deficits in emotion differentiation, which is defined as the tendency to experience vague affective states rather than well-defined emotions [80]. They are also more predisposed to dysfunctional processing of emotions related to food information [81]. In this study, reduced control over emotions and reduced attraction to food pictures were mediated by negative affect, supporting the predictive role of negative affect in ED symptomatology [81].…”
Section: Nonhomeostatic Factors Food Reward and Emotional Eatingmentioning
confidence: 99%
“…Affect subscale of PANAS, like previous studies ( He et al, 2019 , Sierra et al, 2021 ), however, this may not only introduce bias towards negative impacts of working under the new COVID-19 conditions, but also not identify potential beneficial effects. Hence, further longitudinal studies regarding the same topic should be conducted to explore an insightful information.…”
Section: Limitationsmentioning
confidence: 84%
“…Current mood was assessed by a self-assessment manikin (SAM; Bradley and Lang 29 ; Sierra et al 30 ) 9-point scale (1 = very bad ; 9 = very good ) at the beginning of the survey as well as after the case vignette with the selection of standard. Current mood SAM scores were lost for seven participants (3 in the ICD+ group) due to experimenter error.…”
Section: Methodsmentioning
confidence: 99%